2004
DOI: 10.1007/s11938-004-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary treatment of the irritable bowel syndrome

Abstract: Most patients with functional gastrointestinal disorders report that food ingestion appears to exacerbate their symptoms and consequently conclude that they have some form of gastrointestinal food allergy or intolerance. Dietary management of functional gastrointestinal conditions is an attractive therapeutic option for the patient and physician alike because it is safe and economical and empowers the patient to help themselves. However, in practice, dietary manipulation frequently yields rather disappointing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…Post-prandial worsening of symptoms as well as adverse reactions to one or more foods are common [18,19] and dietary elimination can lead to symptomatic improvements in patients with IBS [3,[20][21][22]. Recently, Zar et al [23] have shown elevated IgG titres in IBS patients while Atkinson et al [24] have demonstrated that food elimination based on IgG antibodies may be effective in reducing IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Post-prandial worsening of symptoms as well as adverse reactions to one or more foods are common [18,19] and dietary elimination can lead to symptomatic improvements in patients with IBS [3,[20][21][22]. Recently, Zar et al [23] have shown elevated IgG titres in IBS patients while Atkinson et al [24] have demonstrated that food elimination based on IgG antibodies may be effective in reducing IBS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous studies which confirm IgG hyperreactivity to food antigens in patients with IBS [ 27 , 38 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients adhering to the diet reported considerable improvement that was greater than the improvement observed with the intake of a probiotic. Also other researchers see the point in introducing a diet based on measurements of the levels of IgG antibodies to food antigens in patients with IBS [9,11]. However, a necessity is emphasised to carefully select research tools, i.e.…”
Section: Effects Of Elimination Dietmentioning
confidence: 99%